A Case Report of Oral Syphilis Before and After Management - Abdulhameed Alsarraf; Aisha Almudahkah; Sarah Alabdalrazaq; Qutaibah Alfadalah (Clinical Case Reports)
ABSTRACT Syphilis is a sexually transmitted infection caused by the spirochete bacterium Treponema pallidum, presenting with oral manifestations at various stages of the disease, including primary, secondary, and tertiary phases. Oral manifestations tend to be misdiagnosed as other lesions; therefore, the diagnosis and treatment may be delayed. This case reports the diagnosis and treatment of a 27‐year‐old female patient who presented to the Oral Medicine clinic with oral syphilis, emphasizing the clinical presentation before and after treatment.